Toward cost-effective staffing mixes for Veterans Affairs substance use disorder treatment programs. Issue 1 (June 2015) - Im, Jinwoo; Shachter, Ross; Finney, John; Trafton, Jodie
Abstract Background In fiscal year (FY) 2008, 133, 658 patients were provided services within substance use disorders treatment programs (SUDTPs) in the U.S. Department of Veterans Affairs (VA) health care system. To improve the effectiveness and cost-effectiveness of SUDTPs, we analyze the impacts of staffing mix on the benefits and costs of specialty SUD services. This study demonstrates how cost-effective staffing mixes for each type of VA SUDTPs can be defined empirically. Methods We used a stepwise method to derive prediction functions for benefits and costs based on patients' treatment outcomes at VA SUDTPs nationally from 2001 to 2003, and used them to formulate optimization problems to determine recommended staffing mixes that maximize net benefits per patient for four types of SUDTPs by using the solver function with the Generalized Reduced Gradient algorithm in Microsoft Excel 2010 while conforming to limits of current practice. We conducted sensitivity analyses by varying the baseline severity of addiction problems between lower (2.5 %) and higher (97.5 %) values derived from bootstrapping. Results and conclusions Compared to the actual staffing mixes in FY01-FY03, the recommended staffing mixes would lower treatment costs while improving patients' outcomes, and improved net benefits are estimated from 1472 to 17, 743 per patient.